Background of TELERIEG project - Berthoumieu J.-P. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
Irrigation management is now possible by monitoring plant and soil water status in a special location in a field that is supposed to well represent a larger surface. This place, used as a reference, is often equipped with point sensors (as EnviroScan and others) to measure the precise variation of the available water into the root zone. Completed with weather forecast it enables a decision taking about the best moment and best amount of irrigation, preventing any risk of stress by lack of water or lack of air (brief saturation with anoxia) and reducing diffuse pollution by drainage (see PRECIRIEG project, www.precirieg.net). As it is quite expensive and time consuming to install probes in many locations the TELERIEG (www.telerieg.net) project is trying to reveal the potential of remote sensing tools in order to extend the principles of precise irrigation advice over larger irrigated areas. In this article we describe the different objectives and principal findings that are presented in other papers in this book.